The running ground : a father, a son, and the simplest of sports - Thompson, Nicholas, 1975- (Random House, 2025)
"For Nicholas Thompson, running has always been about something more than putting one foot in front of another. He ran his first mile at age five, using it as a way to connect with his father as his family fell apart. As a young man, it was a sport that transformed, and then shook, his sense of self-worth. In his 30s, it was a way of coping with a profound medical scare. By his early 40s, Thompson had many accomplishments. He was the Editor in Chief of a major magazine; a devoted husband and father; and a passionate runner. But he was haunted by the recent death of his brilliant, complicated father and the crack-up that derailed his father's life. Had the intensity and ambition he'd inherited made a personal crisis inevitable for him as well? Then a chance offer gave him the opportunity to train for the Chicago Marathon with elite coaches. Giving himself over to the sport more fully than ever before, he discovered that aging didn't necessarily put you on an unbroken trajectory of decline. For seven years after his father died, Thompson transforms his body to perform at its highest capacity, and the profound discipline and awareness he builds along the way changes every aspect of his life. Throughout the narrative, he weaves in stories of remarkable men and women who have used the sport to transcend some of the hardest moments in life. The Running Ground is a story about fathers, sons, and the most basic and most beautiful of sports"-- Provided by publisher.